Not just a simple survey: A case study of pitfalls in interdisciplinary, multiorganizational, multinational research for development - Kilwinger, Fleur B. M; Caron, Cynthia M.; Rietveld, Anne M.; van Dam, Ynte K. (Informa UK Limited, 2024)
Surveys are common research methods in agricultural research for development. Despite the multitude of well-documented warnings for pitfalls in survey research, it appears challenging to avoid these in practice. We use a case study in agricultural research for development to illustrate what complicates survey research within an interdisciplinary, multiorganizational and multinational team. The survey research process, rather than the survey outcome, is our object of study. Using the Methodology of Interdisciplinary Research (MIR) framework we identify different steps within survey research. We overlay a technographic lens to understand "the making of a survey". We thereby focus on the transformations made from beginning to end in survey research, the different task-groups involved, and on the norms and rules that guide this process. This illustrates the practice of survey research in diverse and multiform research teams, and shows which vital methodological steps are often ignored, skipped, or overruled. Our findings reveal that the intrinsic complexity of effective survey research is disproportionally exacerbated by the complexity of a diverse and multiform research team. We recommend allocating more resources and attention to capacity strengthening, harmonization, operationalization, capitalizing on different strengths, integration and communication.